Analysis the Critical Factors Causing Wastages of Construction Materials in Building Construction: Analyzing the Causes and Impacts of Construction Material Wastages (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Construction industry has been swiftly developing around the world from last three decadeespecially in India the rate of developing of this industry is very high. There is a lot of capital investment,is invested in this sector as well as this industry become second largest industry after agriculture inIndia in perspective of capital investment as well as employment generation. This industry directlyrelated with GDP of nation. The bigger construction projects have been launched in power,infrastructure, building sector in recent year. The 60 to 70 expenditure of the any construction projectspend on construction materials. And it is found that huge quantity of wastage of material take place onsite during the construction phase. Wastages of material has major problem in construction industrywhich must be recognize very efficiently. Effective control on wastages of material saves money, so thatorganizations profit margin will increase. More specifically, it has main impact on construction cost,construction productivity, time, environment aspect. At such circumstance reduction of wastage ofmaterial during the construction phase contribute major role in economy of that construction project.Impact on environment is also serious issue because due to wastages of material the natural resourceswhich are used for production of that construction material also wasted. The majority of this wastage ofmaterial can be avoided by competent firm control over supervision of site, flow of constructionmaterial strict labour supervision. This study identifies sources for wastages of construction materialand critical factor causing wastages of material for those sources by using Delphi techniques anddetailed questionnaires analysis also states the necessary suggestion for reduction in wastages ofconstruction material and also suggest checklist for reduction of wastages of construction materials.